Effect of sire and environment on growth performance of grade-2 Brahman calves (Journal of the Bangladesh Agricultural University, 2020)
The present study was carried out to evaluate the effect of sire and environment on growth performance of grade-2 Brahman calves. A total of 70 grade-2 Brahman calves produced from 6 sires (14BR0043, 7BR-524, 14BR0040, 7BR-527, 14BR0041,7BR-522) were included in this study to know the effect of different sires on calves growth performances those located on 8 different areas (Barisal, Chattogram, Dhaka, Khulna, Mymensingh, Rajshahi, Rangpur, Sylhet). Analyses were performed by using Statistical Analysis System (SAS) version 9.1.3. Analyses revealed that sires had significant effect (p0.05) was observed on birth weight, 3-month, 9-month and 12-month weights of progeny. The highest mean birth weight (32.27±0.59 kg) and 1-month weight (57.58±2.11 kg) of calves was found from the sire 14BR0040 and 14BR0041, respectively. The highest mean of 3-month (81.57±3.13 kg), 6-month (186.71±6.20 kg), 9-month (332.43±8.07 kg), 12-month (463.57±13.61 kg) and 24-month (903.33±16.71 kg) weights were found by sire 7BR-524, 14BR0043, 14BR0043, 7BR-524 and 14BR0040, respectively. The area significantly (p